TEKS DAN OTORITAS PENAFSIR (Antara Relativitas Interpretasi Teks, dan Perilaku Pemberengusan Sesama) - Jabbar, Luqman Abdul (Khatulistiwa, 2012)
The Qur’an and other religious texts, mainly functioning as guidelines of life for ummah, has always been an inevitable object to study not only by Muslilms but also by non-Muslims. Any religious texts including the Qur’an have a long history. Every approach has been made to learn and understand the meaning contained in the Qur’an. Therefore, it may be interpreted differently by the ummah in various aspects of their life. There is no guarantee from God that the interpretation is absolutely correct. Why, then, do the people who have the authority think that they are always right? And do others not have such authority?